If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-8(8-x)=13
We move all terms to the left:
2x-8(8-x)-(13)=0
We add all the numbers together, and all the variables
2x-8(-1x+8)-13=0
We multiply parentheses
2x+8x-64-13=0
We add all the numbers together, and all the variables
10x-77=0
We move all terms containing x to the left, all other terms to the right
10x=77
x=77/10
x=7+7/10
| 4w^+19w-5=0 | | -3p-8/9=11p+1 | | 120x+32=54-3x | | -7v+10=-39 | | 5-x/8=3-(x-2) | | 3a-4a=6 | | 10+8v=-3(v-7) | | 9x^2-7x-2=) | | -21/28=12a/28 | | 3(4a+2)=3(a-2) | | -y+13÷-48=-40 | | -3(-2x+20)+8(x+12=92 | | 10=1/2n | | -10-11m=13 | | 5(1-5x)+4x=-8x-5(-8x-2x) | | 18+5t=83 | | |3n-5|+13=1 | | (v-6)^2-72=0 | | 5-x/8=3x-(x-2) | | 10(4x-1)=24 | | a÷164363-10=10 | | 5/6b=8 | | 2(4x)*2+3(4x)=0 | | (b-4)=b/2 | | 1/8+x=1/2 | | 28=-4x-4 | | -2(9x-9)+7x=4(x+9) | | x2+6x−18=0 | | 15-5=1/2n | | -3+11y+7=14+15y-18 | | 18-6k=6(1-3k) | | 6n+9=-3n−21−66n+9=-3n-21-6 |